IDENTIFICATION OF GREEN OPEN SPACES USING THE NDVI AND SAVI METHODS IN THE CITY OF METRO - Amri, Resica Permata; Zakaria, Ahmad; Novianti, Tika Christy; Armijon, Armijon (Elipsoida : Jurnal Geodesi dan Geomatika, 2025)
The presence of green spaces in urban areas is a critical issue for Indonesian local authorities, prompting various initiatives aimed at achieving effective and high-quality urban growth. As stipulated by Spatial Planning Regulation No. 26 from 2007, it is mandated that each city must allocate 30% of its total area for green open spaces to foster a productive, secure, pleasant, and sustainable urban setting, with a minimum standard consisting of 20% public green areas and 10% private green areas. This research employs two methods for assessing vegetation density, specifically NDVI and SAVI. These two indices play significant roles in vegetation examination, thus employing both indices is intended to address each method’s limitations, with the expectation that they will yield precise vegetation mapping based on comparative findings. The ultimate area identified for green open spaces is 77.97 hectares, while the green space map for Metro City, derived from the Metro Regional Planning Agency, indicates a total of 110.82 hectares. This produces a percentage discrepancy of 0.70, or 70%. The two maps reveal a disparity between the Research RTH and Bappeda RTH results. The data indicates that the Green Open Space in Metro City spans an area of 110.82 hectares. The NDVI method categorizes Green Open Space with a minimum value range of -0.16 to 0.25. Meanwhile, the SAVI method classifies Green Open Space within a minimal value range of 0.36 to 0.52. Nevertheless, this situation has not been fully optimized due to the presence of rice fields and remained vegetative land cover being recorded. Following the overlay analysis of the Vegetation Density Map, Land Cover, and Rice Fields, rice paddies and urban areas are no longer recognized as Green Open Spaces. Therefore, the Green Open Space in Metro City for the year 2022 is finalized at 77.97 hectares.